The Effect of Remittance, Consumption, and FDI on Economic Growth in ASEAN Countries - Mega Mariska; Lies Maria Hamzah; Arivina Ratih (EKO-REGIONAL, 2021)
One of the main indicators seen in reviewing the relationship between international workers and economic growth is remittances. Remittances obtained from workers abroad are one of the major sources of finance for developing countries. Remittances are also a source of finance in increasing migrant household incomes which encourage improved consumption which will affect economic growth. This study was conducted to explore the impact of migrant remittances, consumption and FDI on economic growth in 10 ASEAN countries using annual panel data from 2015-2019. This study uses panel data regression analysis with the Random Effect Model (REM) approach. The results showed that remittances, consumption and FDI positively and significantly contributed to economic growth in 10 ASEAN countries. Significant contribution of migrant remittances in economic growth if their use is directed to more productive sectors such as use in the investment sector can help the economies of ASEAN countries to maintain and increase economic growth. The government needs to improve the quality of migrant workers through education because a high level of education will affect the level of wages received by migrants and will have an impact on increasing remittances. The limitation in this study is the use of limited data, for 2020 it is not included in the data set used in the analysis. For this reason, further research should use 2020 data because in 2020 there be a new phenomenon, namely COVID-19 which can be traced to the impact of this phenomenon on remittances. Keywords: Remittances, Migrant, Economic Growth, Panel Data